Community of missionary disciples : the continuing creation of the church - Bevans, Stephen B. 1944- (Maryknoll, NY : Orbis Books, 2024)
"Ecclesiology from a mission perspective"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Missions -- Theory; Christian leadership; Catholic Church